ಗಾಜೇಶಲಿಂಗನ ಲೀಲೆ - (:unkn) unknown (Gulbarga University, 2012)
This book is an collection of poems of Gajeshalingana Leele
Gaajeshalingana Leele
Keywords: Kannada; ಗಾಜೇಶಲಿಂಗನ ಲೀಲೆ; Gaajeshalingana Leele; Philosophy; Kannada; Kannada